Sympathetic nerve blocks for posttraumatic stress disorder: an evidentiary review for future clinical trials - Prasad, Sakshi; Jain, Nityanand; Umar, Tungki Pratama; Radenkov, Igor; Ahmed, Sirwan Khalid; Sakagianni, Virginia; Kollia, Sofia; Hingora, Mohmed Junaid; Kumari, Nikita; Akbari, Amir Reza; Renemane, Lubova; Bachu, Anil (Frontiers in Psychiatry, 2023)
Posttraumatic stress disorder (PTSD) is a chronic disorder resulting from exposure to traumatic events. In recent years, sympathetic nerve blocks have gained interest as an emerging treatment modality for PTSD. They have been shown to reduce autonomic dysfunction associated with PTSD symptoms, particularly in refractory and treatment-resistant patients. However, there is limited evidence regarding the technique’s effectiveness in PTSD patients. Therefore, this scoping review was designed to update and summarize the current literature on this topic to inform the design of future clinical trials and studies. Our review of 22 studies (mostly case reports and series) included 1,293 PTSD patients who received sympathetic nerve blocks, primarily military service members and veterans, with a median age of 42.2 years. 0.5% Ropivacaine was the preferred anesthetic, and the right sided stellate ganglion block was the most commonly used technique. Relapse of symptoms was reported commonly, resulting in additional nerve block sessions. Most reported side effects were mild and transient. Despite the encouraging results, we remain cautious in interpreting the benefit of the technique due to the lack of sufficient standardized clinical trial data, heterogeneity in reported results, and the potential for bias in reporting. Future studies should focus on evaluating and addressing the technique’s effectiveness, safety, tolerability, and indications.